Combinatorial PPTase screening and systematic metabolic engineering for high-level indigoidine production in Corynebacterium glutamicum - Jiali Zhang; Zeyu Li; Rui Lu; Junsong Xiao; Yingying Zhu; Wei Xu; Wanmeng Mu (Food Bioscience, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Combinatorial engineering of 2-C-methyl-D-erythritol 4-phosphate pathway flux optimization and key enzymes spatial organization for (−)-α-bisabolol production in Escherichia coli - Junsong Xiao; Zeyu Li; Roulin Chen; Rui Lu; Jiali Zhang; Yingying Zhu; Wanmeng Mu (Food Bioscience, 2026)

Exploration of the resistance mechanism of Botrytis cinerea to pyrimethanil - Liting Wu; Hongjiao Mu; Rui Xiao; Zhiqiu Qi; Rujun Zhou (Journal of Plant Diseases and Protection, 2025)

Phosphorus speciation, controlling factors, and ecological risk assessment in lagoon sediments: a case study of the Shamei Lagoon, Qionghai, Hainan - Kun Yuan; Xuan Mu; Guangning Xiao; Kexin Li; Wantong Zhou; Rui Wang; Shisheng Wang (Frontiers in Marine Science, 2025)
The Shamei Lagoon in Qionghai, Hainan, is an ecologically significant coastal wetland system that has recently faced increasing ecological risks due to phosphorus (P) pollution. In this study, 22 sediment samples were systematically collected from the main lagoon body, river inlets, and the transitional zone to the open sea. A comprehensive approach incorporating standardized phosphorus fractionation, spatial interpolation, redundancy analysis, and ecological risk assessment was used to investigate P speciation, spatial distribution patterns, controlling factors, and ecological risks. The results showed that: (1) Total phosphorus (TP) concentrations ranged from 261.87 to 875.74 mg/kg, with a mean of 415.72 mg/kg, comparable to typical lagoons in China. Inorganic phosphorus (IP) dominated the P fractions (mean: 317.70 mg/kg), with Fe/Al-bound phosphorus (Fe/Al-P, mean: 183.52 mg/kg) markedly exceeding Ca-bound phosphorus (Ca-P, mean: 105.88 mg/kg). Organic phosphorus (OP) had the lowest contribution (mean: 98.02 mg/kg). (2) The primary sources of P pollution were agricultural runoff and aquaculture waste, industrial discharges and vessel leakage, and regional calcareous deposition. High TP and OP concentrations were concentrated in the southwest river inlet zone, directly linked to fertilizer runoff and tourism-related wastewater. IP levels were elevated in the southern region, driven by hydrodynamic processes. Fe/Al-P was enriched in the central lagoon, likely associated with oil degradation from vessels. Secondary peaks of Ca-P occurred in the southwest aquaculture zone and the northeastern mangrove area, attributed to feed residues and shell debris, respectively. (3) Cation exchange capacity (CEC) was identified as the primary controlling factor for spatial variation in P speciation (explained variance: 46.0%, p < 0.01), followed by organic matter (OM), while pH exhibited a marked negative regulatory effect. (4) At 45.5% of sampling sites, TP levels exceeded the ecological safety threshold (600 mg/kg), and 18 sites, mainly located near the river mouth and central lagoon, were classified as heavily polluted, posing a threat to aquatic ecological security. These findings indicate that sediment P pollution in the Shamei Lagoon is driven by multiple anthropogenic activities. Mitigation strategies should prioritize control of agricultural non-point sources, aquaculture residues, and vessel oil pollution, along with sediment remediation focused on enhancing CEC.

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

The molecular basis of heat stress responses in plants - Yi Kan; Xiao-Rui Mu; Jin Gao; Hong-Xuan Lin; Youshun Lin (Molecular Plant, 2023)

Global prevalence and factors affecting the level of Cryptosporidium contamination in soil: A systematic review, meta-analysis, and meta-regression - Mu-Ran Zuo; Xiao-Ting Li; Rui-Zhe Xu; Wen-Chao Sun; Hany M. Elsheikha; Wei Cong (Science of The Total Environment, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

A bacterial polysaccharide biosynthesis-related gene inversely regulates larval settlement and metamorphosis of Mytilus coruscus - Li-Hua Peng; Xiao Liang; Rui-Heng Chang; Jia-Yi Mu; Hui-E Chen; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang (Biofouling, 2020)

Effects of light curing modes and ethanol-wet bonding on dentin bonding properties - Mu-zi Li; Jin-rui Wang; Hong Liu; Xia Wang; Kang Gan; Xiu-ju Liu; De-li Niu; Xiao-qing Song (Journal of Zhejiang University-SCIENCE B, 2016)